Zr-doped ZnO nanohybrid via glycine mediated sol–gel approach as benign supporter for degradation of Crystal violet and antibacterial performance - S. Gouthamsri; M. Ramanaiah; K. Basavaiah; K. Jaya Rao (Results in Chemistry, 2023)
The current work describes the preparation of zirconium-doped zinc oxide (Zr/ZnO) nanohybrid through sol–gel approach fascinated by combustion process with glycine as a fuel. The analytical instruments were used including FTIR, XRD, XPS, SEM, BET and TGA for studying the optical and structural properties of prepared nanohybrid. The characterized Zr-ZnO nanohybrid exhibited lesser size (18 nm) than pure ZnO (24 nm). This could be a lead to possess more catalytic activity towards the degradation of dye pollutants and inactivation of pathogens. The photocatalytic performance was executed by the degradation of Crystal violet (CV) dye under visible light irradiations, the complete degradation was achieved in 90 min. The optimum reaction conditions are 0.1 g catalyst dose, pH-2, and 10 ppm dye concentration. To extent on catalytic performance, the antimicrobial study was further carried out by Vibrio cholera, and Clostridium perfringes. The results declared that prepared nanohybrid was the most effective for antimicrobial performance.